Challenges and Opportunities Facing Students of Field Training in Social Work through e-Learning during the COVID-19 Pandemic: A Social Study on a Sample of Students of Al-Balqa Applied University - Al-Bakar, Asem (Dirasat: Human and Social Sciences, 2022)
The study aims at identifying Challenges and opportunities facing students of field training in social work through e-learning during the COVID-19 pandemic: a social study on a sample of students of Al-Balqa Applied University. The study sample consisted of (64) trainees, who were selected by the social survey method through comprehensive inventory. Descriptive statistical methods and the multiple variance test were used. Results showed that the most important challenges faced by the students were the presence of challenges brought about by the pandemic, including the inability of the trainee to meet the client in social institutions, in addition to challenges such as using the computer and lack of a network of communication, also, student’s inability to apply what they learned in theory. Opportunities included remote field training facilitated communication in social institutions. The field training showed the importance of using digital technology to help clients during crises. Among the average level opportunities was the increase of opportunities of getting acquainted with the experiences of national and international social institutions. The results have shown that there were no statistically significant differences at (0.05≥α) in the level of challenges for the distance-trained students, according to their opinion, as attributed to the variables of gender, academic level and level of field training.